Natal and neonatal teeth: Review of the literature - Cunha, Robson Frederico [UNESP]; Boer, Farli Aparecida Carrilho [UNESP]; Torriani, Dione Dias [UNESP]; Frossard, Wanda Terezinha Garbeline [UNESP] (My University, 2001)
Child development from conception through the first years of life is marked by many changes. Tooth eruption follows a chronology corresponding to the date when the tooth erupts into the oral cavity. These dates have been established in the literature and are subjected to small variations depending on hereditary, endocrine and environmental features. At times, however, the chronology of tooth eruption suffers a more significant alteration in terms of onset, and the first teeth may be present at birth or arise during the first month of life. The expectations about the eruption of the first teeth are great and even greater when the teeth appear early in the oral cavity. The objective of the present study was to present a review of the literature with important aspects about natal and neonatal teeth.
Keywords: differential diagnosis; human; newborn; pathology; review; tooth eruption; tooth extraction; tooth malformation; Diagnosis, Differential; Humans; Infant, Newborn; Natal Teeth; Tooth Eruption; Tooth Extraction; Tooth, Supernumerary